(untitled) (Homoeopathy for All, 2026)
The Samuel Hahnemann Monument is a Neoclassical memorial located at Scott Circle NW in Washington, D.C.. Dedicated on June 21, 1900, it honors the founder of homeopathy, Samuel Hahnemann, and was designed by sculptor Charles Henry Niehaus and architect Julius Harder. It features a seated bronze statue on a granite exedra with colorful Italian glass mosaic tiles.